Fatores motivacionais para a escolha do curso de Pedagogia no IEAA/UFAM - Castro, Natália Gomes (Brasil, 2021)
Motivation is a psychological variable that has been studied for several years, including by scholars in the educational field. In general, it is defined as a driving force and maintainer of behaviors. Although we cannot see the motivation itself, we do see people's behaviors and we can infer how motivated or discouraged they are. However, what motivates this observed behavior, we cannot determine from this observation, measurement instruments (tests, scales) or conversations are necessary in which the individual can report what makes him act in a certain way, that is, his motivations . This study aimed to assess the motivation of students in the pedagogy course at IEAA / UFAM. The instrument used was the EMA scale. The results indicate that students are still extrinsically motivated, although at a level that moves towards intrinsic motivation, which is a positive result, since they are looking for autonomy, freeing themselves from rewards as a motivating source.